การรับรู้และการยอมรับศูนย์บริการสารสนเทศชุมชนในชุมชนชนบทไทย - ศรัณย์ธร ศศิธนากรแก้ว (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This research study aims at examining psychological factors relating to the perception and the decision to use telecenters as well as proposing a model to explain the telecenter adoption phenomenon of individuals in Thai rural areas. The study looks at 3 telecenters : 1) Ban Fon Telecenter 2) Ban Sam Kha 3) T-Centre Jakkarach by using both quantitative and qualitative research methods. Data were collected using questionnaires and in-depth Interview and were analyzed and presented as frequency distributions, percentages, means and standard deviations along with data from the interviews. The differences between the telecenter users and the non users were tested using t-test, Pearson product moment correlation and linear multiple regression using LISREL The results indicate that most of the users were students and college students who came to the telecenter for their study-related tasks. The non-users were primarily employees with low income and low education and,thus, information technology was not a necessity for them. Both users and non users differed significantly at 0.01 level in terms of computer self-efficacy, perceived usefulness, perceived ease of use, compatibility, and behavioral intention .In addition, all variables significantly indicated positive correlation at 0.01 level. Path analysis found that the variables which had positive direct effect towards using behavior were computer self-efficacy (0.29), behavioral intention (0.20) and perceived usefulness (0.14). Computer self-efficacy, perceived usefulness, perceived ease of use and compatibility had direct influence towards behavioral intention at 0.23, 0.11, 0.03 and 0.27 accordingly. Apart from direct usage there was indirect usage through the community radio, facilitator, non- formal education and other community activities.